2021
DOI: 10.3390/nano11082005
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Selenium Nanoparticles: Potential Solution to Oxidative Stress Mediated Inflammation in Rheumatoid Arthritis and Associated Complications

Abstract: Rheumatoid arthritis (RA) is a common chronic inflammation-mediated disorder having systematic complications. RA triggers a self-directed inflammatory and immunological cascade that culminates in joint destruction. Though a range of treatment options are available, none of them are without adverse effects and this has led researchers to search for alternative solutions. Nanomedicine has emerged as a powerful therapeutic alternative, and selenium (Se) is an essential micronutrient trace element that has a cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 159 publications
(188 reference statements)
0
26
0
Order By: Relevance
“…Thus, it has been shown that the effectiveness of chitosan as an antitumor and antioxidant compound strongly depends on the characteristics of SeNP [ 35 ]. The method of their production also affects the size and shape of SeNP, which can significantly determine their pharmacological properties [ 36 ]. Using biosynthesis or chemical synthesis, SeNP with a hexagonal ring structure and rod-like, spherical, or flower-like shapes can be produced.…”
Section: The Main Methods Of Obtaining Selenium Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it has been shown that the effectiveness of chitosan as an antitumor and antioxidant compound strongly depends on the characteristics of SeNP [ 35 ]. The method of their production also affects the size and shape of SeNP, which can significantly determine their pharmacological properties [ 36 ]. Using biosynthesis or chemical synthesis, SeNP with a hexagonal ring structure and rod-like, spherical, or flower-like shapes can be produced.…”
Section: The Main Methods Of Obtaining Selenium Nanoparticlesmentioning
confidence: 99%
“…RA is a common chronic inflammation-mediated and systematic autoimmune disorder. It is a long-lasting condition described as inflammation of diarthrodial joints leading to symmetrical polyarthritis and synovial hyperplasia (swelling) that results in the progressive destruction of cartilage and bones and the loss of articular function that leads to the eventual deformation of joints [ 36 ]. SeNP reverted the GPx1, CAT, and COX-2 mRNA expression and restored the levels of TNF-α, IL-1β, IL-6, and MCP-1 [ 199 ] and can be a promising method of RA therapy.…”
Section: The Role Of Senp In Medicine and Human Healthmentioning
confidence: 99%
“…In this scenario, the innovative Se nanomedicine has also shown that the production of SeNPs could be employed in a number of applications. NPs are characterized by low toxicity, and significant and selective effects are obtainable with very small quantities, namely a substantially reduced risk of toxicity in the face of a high antiviral capacity [ 18 , 19 ]. Recent in vitro data have reported that treatment with the antiviral drug oseltamivir, in combination with SeNPs, can increase cell viability to prevent Enterovirus 71 infection and reduce apoptosis (via the Bax signaling pathway) [ 131 ].…”
Section: Role Of Selenium In Covid-19: Clinical Significance and Impl...mentioning
confidence: 99%
“…Furthermore, innovative Se nanomedicine has shown that the production of Se nanoparticles (SeNPs), characterized by low toxicity and significant and selective effects obtainable with very small quantities (greatly reduced risk of toxicity in the face of high antiviral capability), may represent a promising opportunity [ 18 , 19 ]. In fact, SeNPs have been found able to reduce oxidative stress, promote apoptosis (killing cancer cells), modulate immune activity, and exert efficacious antimicrobial and antiviral activity, and as such, they may have potentially beneficial applications in the COVID-19 context [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…GPx and other selenoenzymes are the major Se-containing antioxidants in the body that help to neutralize ROS [54]. The expression of selenoproteins is specific to various tissues and depends on Se availability in feed [55]. Selenoproteins help animals resist oxidative stress, which can be caused by, heat, decreased productive performance, and various diseases (e.g., mastitis and intramammary infections in dairy cattle).…”
Section: Selenium Absorption and Bioavailabilitymentioning
confidence: 99%